The impact of the 2011 UK post-exposure prophylaxis for HIV following sexual exposure guidelines: a regional retrospective audit. (September 2015) - Bennett, A; Wainwright, E; Lord, E; Oduru, M; Chen, F; Desmond, N; Sherrard, J; Duncan, S
A re-audit of prescribing of post-exposure prophylaxis for HIV following sexual exposure in the Thames Valley demonstrated that an updated proforma has led to significant improvements in clinician-led outcomes, but had no impact on completion or follow-up rates.